PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN QUIZIZZ TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DI SMK SWASTA AL-MA'SHUM SIDODADI - Raffi Azizi; Ely Syafitri (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
The study aims to analyze the effect of the Discovery Learning model assisted by the interactive media Quizizz on students' critical thinking skills in mathematics at SMK Swasta Al-Ma'shum Sidodadi. The main background of this study is the low level of students' critical thinking skills in solving complex problems. The research method used was a quasi-experimental design with a nonequivalent control group design. The research sample consisted of the experimental class (Xth-2) implementing the Discovery Learning model assisted by Quizizz and the control class (Xth-1) using direct learning. Data were collected through a critical thinking skills test in the form of essay questions measuring indicators of interpretation, analysis, evaluation, and inference. The results of the data analysis showed a significant increase in the average critical thinking skills in the experimental class (80.65) compared to the control class (66.41). Hypothesis testing using an Independent Samples T-Test in SPSS 20 yielded a significance value of 0.000 < 0.05. These findings confirm that the integration of the discovery learning model with the Quizizz gamification media has a significant positive impact on improving students' critical thinking skills.